Comparison of Bank Efficiencies between the US and Canada: Evidence Based on SFA and DEA - Ruinan Liu (Journal of Competitiveness, 2019)
This paper aims to achieve two targets. First, using balanced panel data from 2008 to 2017 it compares the cost efficiencies between US and Canadian commercial banks to examine whether structural differences in the two countries’ banking industries create differences in efficiencies. Since efficiency is a valuable measurement to indicate the ability of an organization to utilize limited resources to produce, in this article we compare the operating competitiveness of these banks. Next, to achieve the first goal, both the Stochastic Frontier Analysis and Data Envelopment Analysis are employed to examine cost efficiencies in order to find new evidence given the mixed results in previous literature. Profit efficiency is also compared with cost efficiency based on a parametric approach. The results regarding cost and profit efficiency conforms to prior studies indicating a relatively low correlation. However, SFA and DEA produce very different and uncorrelated results, though DEA generates overall lower efficiencies, as expected. Thus, the findings suggest that methodology cross-checking along with information regarding variables selection are necessary before decision making. Essentially, there is not enough evidence to conclude that bank efficiencies are different either between the US and Canada, or between large and small banks in US. However, DEA suggests an increasing trend in average efficiencies, as this parameter is not time-adjusted. A more technical exploration of how to reliably measure efficiencies is awaited to make advancements in this area.